Public sector coordination in Papua New Guinea: responsibilities and experience of central coordination agencies - Ata, Robyn (2018)
This article focuses on agencies at the centre of government in Papua New Guinea with specific responsibilities for fostering policy and administrative coordination. Of particular interest are levels of inter-agency collaboration, along with factors affecting the effectiveness with which coordination can be achieved, both horizontally at the centre and vertically between the centre and subnational administrations. The experience to-date confirms the definite need for the arrangements to be reviewed and transformed with the aim of considerably enhancing their efficacy. - Reproduced.
Keywords: Public administration